The Nautical Magazine for 1874 (Cambridge library collection. Nautical magazine, 1874)
The Nautical Magazine first appeared in 1832, and was published monthly well into the twenty-first century. It covers a wide range of subjects, including navigation, meteorology, technology and safety. An important resource for maritime historians, it also includes reports on military and scientific expeditions and on current affairs. The 1874 volume continues the previous year's attacks on attempts by Samuel Plimsoll to introduce seaworthiness inspections and other safety regulations, arguing for 'individual responsibility' rather than 'maternal interference by the State in the business concerns of daily life'. In addition to covering these debates, this volume concludes the series of articles on 'great ports' and begins one on 'our colonies'. It also contains the latest statistics on shipbuilding, substantial updates on steam technology, notes on a fascinating selection of court cases, and a song claimed to be highly effective in teaching trainee seamen the 'rule of the road at sea'